Eigentum und Geschlecht Jüdische Unternehmerfamilien in Wien (1900-1960) - Niederacher, Sonja (2012)
This book examines the financial circumstances of Jewish men and women in Vienna from the turn of the century to 1938, focusing on gender as a social category. The central issue is the extent to which the amount and, above all, the category of assets were structured according to gender. Furthermore, the gender specifics of financial withdrawals by the National Socialists and restitution and compensation payments after 1945 shall be examined. Three subject areas will be carefully covered for the period before 1938, in which structured relevance is accorded to the category of gender. These are economic activity, which includes gainful employment and entrepreneurial activity, inheritance practices, and marriage as an influential financial factor. The study is based on a sample of 788 individuals (337 women, 451 men), who were affected by National Socialist proprietary measures, i.e. looting policy, in 1938. The sample was drawn for a study by the Austrian Historical Commission. It includes the assets of these 788 people on April 27, 1938 as they were recorded in the so-called assets declaration with which all people defined as Jewish had to declare their property to the authorities. The sample, which has been entered into a database, includes further data on restitution and compensation. This paper will evaluate the data in terms of gender for the first time. Moreover, the financial situation of 78 of the 788 individuals (Sample II) and their familial environment, in particular their parents and siblings, are researched through further sources including inheritance files, wills, marriage contracts, and commercial and land registers. One of the objectives is to investigate the origin of the assets declared in 1938. Based on the selection of individuals, which was dependent upon the existence of a minimum asset level, there are no significant differences between the asset volume of men and women from the sample. Nevertheless, the study points out that the composition of the assets, which means the occurrence and scope of different categories of assets, was determined by gender specific factors. Inheritance practices and segregated access to asset acquisition, particularly in economic activity, are identified as reasons for this. Gender specifics in real estate and business as well as asset transfers between generations and married couples are elaborated upon in detail. Dowries not only influenced the financial situation of the wife or widow and her husband, but also presented essential financial resources for companies. The possibility of economic activity and thereby acquisition of assets is of particular importance; this possibility is primarily decided in the family, as is shown in the individual case histories. Although gender specific differences can hardly be verified in National Socialist asset withdrawal, they can be documented in the National Socialists' approach to mixed couples. The restitution results are influenced by several factors; among these are also the claimed asset categories. In a comparative evaluation of men and women, the restitution results reflect the success of the respective asset categories.